2014
DOI: 10.1080/08985626.2014.992374
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the enclave? Break-outs into mainstream markets and multicultural hybridism in ethnic firms

Abstract: The literature on immigrant entrepreneurship has richly described the characteristics and peculiarities of ethnic businesses catering to enclave markets. However, several indications suggest that immigrant-owned firms are increasingly entering mainstream markets and changing both their internal structures and their external networks with resource providers. One of the most substantial changes, which has been overlooked by researchers, consists of the appearance of what we define as 'multiculturally hybrid firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 80 publications
(86 reference statements)
6
69
2
Order By: Relevance
“…This might even be the case for highly educated migrants. Arrighetti, Bolzani, and Lasagni (2014) observed that so-called multicultural hybrid firms which deployed "ethnically diverse human resources at the management and personnel levels" stand a greater chance of survival which may indicate that they indeed are able to gather richer information by bridging distinct networks. Our logistic regression analysis indicated that the length of stay is a significant factor in determining the chances for survival of the Ghanaian businesses.…”
Section: Discussionmentioning
confidence: 99%
“…This might even be the case for highly educated migrants. Arrighetti, Bolzani, and Lasagni (2014) observed that so-called multicultural hybrid firms which deployed "ethnically diverse human resources at the management and personnel levels" stand a greater chance of survival which may indicate that they indeed are able to gather richer information by bridging distinct networks. Our logistic regression analysis indicated that the length of stay is a significant factor in determining the chances for survival of the Ghanaian businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be felt that the market opportunities within the mesosphere, do not just relate to markets for products, but in encompassing the labour market, opportunities to access skills and knowledge should also be considered. Evidence from Italy suggests that as discussed above language skills are a key factor in the use of labour from a variety of cultures along with management experience (Arrighetti et al, 2014).…”
Section: Challenges Faced By Ethnic Entrepreneurs -Communication Skilmentioning
confidence: 99%
“…Thus, a perspective may be that opportunities in the mesosphere don't just relate to customers, but also in acquiring labour with diverse skills (Bates, 2011;Arrighetti et al, 2014).…”
Section: Macrosphere Factors Causing Shortage Of Suitable Employeesmentioning
confidence: 99%
“…Linguistic distance is an important element of psychic distance, and it has separate and complex influences on modes of entry (Cuypers, Ertug, & Hennart, 2015). Essentially, language skills have been identified by several researchers as an important capability for immigrant entrepreneurs to start up businesses (Brenner, Menzies, Dionne, & Filion, 2010;Mora & Dávila, 2005), move from ethnic markets into the mainstream market (Arrighetti, Bolzani, & Lasagni, 2014), and enter global markets (Sui et al, 2015). With large psychic distance and cultural distance, immigrant entrepreneurs are likely to require greater capability to adapt to culture.…”
Section: Embedded In Two Culturesmentioning
confidence: 99%
“…An individual's cognition can be explored with reference to self-assessed capabilities, which some researchers group into specific capabilities (Ucbasaran et al, 2008), such as social skills that are also crucial to entrepreneurs (Hartog, Van Praag, & Van Der Sluis, 2010). To immigrant entrepreneurs, who move to a new country, a local language skill seems important for them to access resources and move within the labour market (Arrighetti et al, 2014). Skills, which often refer to specific abilities, can be either broadly or narrowly construed, while ability is a relatively stable broad characteristic of individuals (Bird, Schjoedt, & Baum, 2012).…”
Section: Human Capital Theory -Capabilitymentioning
confidence: 99%